Апробация ренормгрупповой модели нестационарной турбулентности - Авраменко, А.А. (Доповіді НАН України, 2011)
На основі RNG k−ε моделі турбулентності для нестаціонарних потоків проаналізовані два типи течій. Перша задача — це осцилююча течія у плоскому каналі, друга — розгінна течія у плоскому каналі. Отримані результати дозволяють визначити область значень параметрів, у якій необхідно брати до уваги ренормалізаційну нестаціонарну поправку турбулентних течій. Two types of flows are analyzed on the basis of the RNG k−ε model of turbulence for unsteady streams. The first problem is the oscillating flow in a flat channel; the second one is the up-start flow in a flat channel. The results allow defining the range of parameter values, in which the account of renormalization unsteady corrections to turbulent flows is necessary.